2021
DOI: 10.1177/14651165211023832
|View full text |Cite
|
Sign up to set email alerts
|

Noncompliance risk, asymmetric power and the design of enforcement of the European economic governance

Abstract: In the European Union, states can distribute enforcement prerogatives between a supranational agency, over which they exercise equal influence, and a Council of ministers, where power resources mostly vary by country size. What shapes attitudes towards different enforcement designs? States at greater risk of noncompliance should eschew deeper cooperation and prefer procedures over which they can exercise more influence. Employing an original data set of positions on relevant contested issues during the negotia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…This outcome is consistent with the political economy or political science literature looking at the background of different enforcement designs of supranational agencies. In particular, Franchino and Mariotto (2021) argue that EU governments anticipating a greater risk of non-compliance will prefer a soultion that offers greater discretion, and countries with higher voting power push for a stronger involvement of the Council.…”
Section: Survey On National Correction Mechanismsmentioning
confidence: 99%
“…This outcome is consistent with the political economy or political science literature looking at the background of different enforcement designs of supranational agencies. In particular, Franchino and Mariotto (2021) argue that EU governments anticipating a greater risk of non-compliance will prefer a soultion that offers greater discretion, and countries with higher voting power push for a stronger involvement of the Council.…”
Section: Survey On National Correction Mechanismsmentioning
confidence: 99%
“…It has also been suggested that the enforcement process is politicized and the strategic conduct of the Commission is influenced by political considerations (Cheruvu, 2022;Kelemen & Pavone, 2021;Toshkov, 2019). Such concerns have also been expressed with regard to the operation of other enforcement tools in the arsenal of the EU, namely those related to economic governance (the Stability and Growth Pact, SGP) (Franchino & Mariotto, 2021;van der Veer, 2022) and for enforcing rule of law in particular (Closa, 2019). This raises the question why the EU institutions do not use the full force of the enforcement tools at their disposal to punish states that do not comply with the EU treaties, laws and policies.…”
Section: Introductionmentioning
confidence: 99%